The nature of fast radio bursts. (November 2018) - Pen, Ue-Li
Physical constraints on the sources of fast radio bursts are few, and therefore viable theoretical models are many. However, no one model can match all the available observational characteristics, meaning that these radio bursts remain one of the most mysterious phenomena in astrophysics.